HTML & XHTML : the definitive guide - Kennedy, Bill, 1951- (O'Reilly, 2006)
" ... Lucid, in-depth descriptions of the behavior of every HTML tag on every major browser and platform, plus enough dry humor to make the book a pleasure to read."--Edward Mendelson, PC Magazine "When they say 'definitive' they're not kidding."--Linda Roeder, About.com Put everthing you need to know about HTML & XHTML at your fingertips. For nearly a decade, hundreds of thousands of web developers have turned to HTML & XHTML: The Definitive Guide to master standards-based web development. Truly a definitive guide, the book combines a unique balance of tutorial material with a comprehens.